Modeling non-convex costs in an LP (for traffic engineering on WANs) - Kandula, Srikanth; Lucier, Brendan; Menache, Ishai; Singh, Mohit (2015)
We describe a Traffic Engineering (TE) solution which can incorporate non-linear link costs. TE decides on the actual assignment of requests' flow to (time, path) pairs.